Political Engagement by ‘apolitical’ Female European Lawyers: The International Federation of Women Judges and Lawyers, 1928 – 1956 - Sara L. Kimble (Clio@Themis)
In 1929, the International Federation of Women Judges and Lawyers became an affiliated organization eligible to lobby delegates at the League of Nations. This transnational legal sorority was dedicated to universal legal reform to address the fundamental problem of sex inequality under the law. The female jurists were part of an interwoven transnational movement seeking to establish a feminist jurisprudence based on equity. Despite global vicissitudes of the interwar era, they called upon the authority of the state and international law to protect the vulnerable, ameliorate suffering, and institute equity.